IDENTIFICATION OF DEGRADED LAND FOR DETERMINATION OF CONSERVATION AREAS BASED ON GIS IN REGION-1 LAMPUNG SELATAN DISTRICT - Armijon Armijon (Engineering Faculty Universitas Lampung, 2020)
Based on a field survey at the beginning of 2019, it shows that the growth and development of land use in the South Lampung Regency area leads to uncontrolled conditions, causing disruption of land function both in the area itself and the area below. This condition can be overcome by making efforts to determine land conservation areas. One of the study documents to determine conservation areas in an area is the distribution of degraded land, so a study of degraded land is absolutely necessary. GIS technology can be used to answer the challenge of determining critical land through the superimpose method using several map layers with weighting techniques. The superimpose study requires data on thematic maps and the distribution of existing land cover. Remote sensing technology is utilized to produce existing land cover maps through classification and image interpretation techniques. Thematic map data supporting other analyzes utilize spatial data from the RTRW of the research area. The largest distribution of degraded land is in Merbau Mataram and Katibung districts which require immediate action to be implemented by the Conservation program. Conservation areas that have been defined in RTRW must be maintained, it is necessary to establish additional protected areas on the Sutet border area. As a disaster mitigation effort, all disaster areas need to be designated as conservation areas.